dc Magnetometry with Engineered Nitrogen-Vacancy Spin Ensembles in Diamond - Balasubramanian, Priyadharshini; Osterkamp, Christian; Chen, Yu; Chen, Xiuliang; Teraji, Tokuyuki; Wu, E; Naydenov, Boris; Jelezko, Fedor (Nano letters, 2019)
The exquisite optical and spin properties of nitrogen-vacancy (NV) centers in diamond have made them a promising platform for quantum sensing. The prospect of NV-based sensors relies on the controlled production of these atomic-scale defects. Here we report on the fabrication of a preferentially oriented, shallow ensemble of NV centers and their applicability for sensing dc magnetic fields. For the present sample, the residual paramagnetic impurities are the dominant source of environmental noise, limiting the dephasing time (T2 *) of the NVs. By controlling the P1 spin-bath, we achieve a 4-fold improvement in the T2 * of the NV ensemble. Further, we show that combining spin-bath control and homonuclear decoupling sequence cancels NV–NV interactions and partially protects the sensors from a broader spin environment, thus extending the ensemble T2 * up to 10 μs. With this decoupling protocol, we measure an improved dc magnetic field sensitivity of 1.2 nT μm3/2 Hz–1/2. Using engineered NVs and decoupling protocols, we demonstrate the prospects of harnessing the full potential of NV-based ensemble magnetometry.